Da trajetória da política habitacional ao encontro do programa Minha Casa Minha Vida em São Leopoldo - Sampaio, Valdirene Palmeira Malaggi (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation is a result of a research that aimed to analyze the current housing policy developed in the city of São Leopoldo, throughthe implementation e execution of housing projects, taking into consideration an unequal occupation of urban spaces, perceived by beneficiariesand managers, regarding to Minha Casa Minha Vida project.That said, matters to ask, if the program subjected to this study, is a good answer for democratization of the production of new housing, with access to urban spaces and services, through public funding and by removing barriers imposed by market. The research is outlined by a case study that mixes, at the same time, field research with the residents of Residencial Mauá II and documentary research. The methodological procedures used were: field observation and interviews. To understand the different contents that compose the theme of this study this workwas structured in theoretical-analitical categories that comprehend the question of social segregation as a configuration element of the social differences reproduced in urban space.It focuses on the thematic of public policy, where the relation between civil society and state is approached while reconstructing the track of housing policy both in national and local ranges. Finally, the union between theory and empiricism, which conforms and analyzesthe perception of beneficiaries, managers and technicians. Among the results, stands out social segregation as a challenge to break with unequal access to the benefits of many social policies. The pattern of housing production being used for the low-income population did not renew aspects of urbanism asmuch as the new demand, weakening the network services and the urban space itself. It was observed and important advance in the history of housing policy, nevertheless it is important to pay attention in the interference of building companies, that leveraged by real state financialization, play a decisive role in the project execution.
Keywords: Segregação socioespacial; Política pública; Habitação; Mercado imobiliário; Social spacial segregation; Public policy; Housing; Real state market; ACCNPQ::Ciências Humanas::Sociologia